The housing channel of intergenerational wealth persistence - Ella Getz Wold; Knut Are Aastveit; Eirik Eylands Brandsaas; Ragnar Enger Juelsrud; Gisle James Natvik (Norges Bank, 2024)
We use Norwegian tax data and a life-cycle model with housing to study how wealth transmits across generations through the housing market. After controlling for a rich set of attributes, households with richer parents are nearly 15% more likely to be homeowners at age 30. Moreover, when entering, they have higher leverage and buy homes worth 15% more. Estimates using international stock market returns as a shiftshare instrument support a causal interpretation. We further document that housing outcomes when young are important determinants of midlife wealth. This holds also when using plausibly exogenous variation in homeownership caused by the timing of intra-family deaths. As a result, housing gaps caused purely by parental wealth explain 12% of intergenerational wealth persistence, making housing equally important as the combined impact of a wide range of household characteristics including income and education. We explore new mechanisms for parental support, such as intra-family housing transactions below market value. Through the lens of our model, house price expectations stand out as a key driver of the magnitude of the housing channel of intergenerational wealth persistence.
hdl:11250/3166797
Keywords: D31; E24; G51; R21; 330; Housing market; intergenerational wealth; wealth inequality